Initial testing (stage 1) of ganetespib, an Hsp90 inhibitor, by the pediatric preclinical testing program1. Issue 7 (9th January 2013) - Lock, Richard B.; Carol, Hernan; Maris, John M.; Kang, Min H.; Reynolds, C. Patrick; Kolb, E. Anders; Gorlick, Richard; Keir, Stephen T.; Billups, Catherine A.; Kurmasheva, Raushan T.; Houghton, Peter J.; Smith, Malcolm A.
Abstract Ganetespib, an Hsp90 inhibitor, was tested against the PPTP in vitro cell line panel and selected xenografts in vivo, including JAK2‐ and BRAF‐mutated models. Ganetespib demonstrated potent in vitro cytotoxic activity (median rIC50 8.8 nM, range 4.4–27.1 nM). In vivo, ganetespib induced significant differences in EFS distribution for 4 of 11 xenografts. Intermediate activity (EFS T/C > 2) was noted only for the MV4;11 xenograft, and there were no objective responses. Administered as single agents, Hsp90 inhibitors examined by the PPTP have shown limited evidence for a therapeutic window against both solid tumor and leukemia pediatric preclinical models. Pediatr Blood Cancer 2013; 60: E42–E45. © 2013 Wiley Periodicals, Inc.